Holacracy, a modern form of organizational governance predictors for person-organization-fit and job satisfaction - Weirauch, Lena; Galliker, Sibylle; Elfering, Achim (Frontiers in Psychology, 2023)
Abstract This study compares illegitimate tasks and appreciation in traditional work organisations and holacracy work organisations based in Switzerland and Germany. In addition, the study tests whether the fit between employees and holacracy organisations depends on personality characteristics. Ninety-five employees working in holacratic companies participated in an online survey with standardised questionnaires on illegitimate tasks, Big Five personality dimensions, perceived holacracy satisfaction and person–organisation fit. For the comparison of illegitimate tasks, a propensity-matching comparison group of people working in traditional companies was used. The results revealed significantly lower illegitimate tasks t(53) = -2.04, p < .05, with a lower level (2.49) in holacracy than in traditional work (2.78). As evidence of this, the results showed significantly higher values for holacratic (5.33) than for traditional work (4.14, t(53) = 4.86, p < .001). Multiple linear regression of holacracy satisfaction on personality dimensions showed neuroticism (b = -4.72, p = .006) as a significant predictor. Agreeableness showed marginally significant results (b = 2.39, p = .06). This indicates that people scoring low on neuroticism and high in agreeableness may thrive better in holacracy organisations. Based on the results, theoretical and practical implications as for example implications for corporates hiring strategy, are discussed. Finally, this study presents numerous directions for future research..